2002
DOI: 10.1021/ol020225+
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Osmium Tetroxide in Polyurea

Abstract: [reaction: see text] Osmium tetroxide has been microencapsulated in a polyurea matrix using an in situ interfacial polymerization approach. These microcapsules have been effectively used as recoverable and reusable catalysts in the dihydroxylation of olefins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Microencapsulated OsO 4 can function as a reservoir and an efficient scavenger of homogeneous catalytic species [42,43]. Hence, it gives results comparable to those achieved by its homogeneous analog.…”
Section: Microencapsulated Osomentioning
confidence: 97%
See 1 more Smart Citation
“…Microencapsulated OsO 4 can function as a reservoir and an efficient scavenger of homogeneous catalytic species [42,43]. Hence, it gives results comparable to those achieved by its homogeneous analog.…”
Section: Microencapsulated Osomentioning
confidence: 97%
“…Ley et al demonstrated that this type of microencapsulated OsO 4 catalyzed dihydroxylation of various alkenes using NMO as the oxidant [42]. Five times recycling was achieved with good yield (74-88%).…”
Section: Microencapsulated Osomentioning
confidence: 99%
“…Osmium tetroxide was encapsulated using polyurea microcapsules by in situ interfacial polymerization of oil-in-water emulsions. [11] The osmium catalyst (Os EnCat) was successfully applied to the non-enantioselective dihydroxylation, but asymmetric dihydroxylation was not described.…”
Section: Microencapsulationmentioning
confidence: 99%
“…doi:10.1016/j.jorganchem.2005.04.025 of osmium leaching [7]. Other efficient approaches have been described: microencapsulation of osmium catalyst in polystyrene [8], polyurea (achiral version) [9], anchoring in poly(ethylene glycol) matrixes [10], silica tetrasubstituted olefins [11], ion exchangers [12], nanocrystaline magnesium oxide [13] anchoring in Amberlite containing residual vinyl groups [14], gold colloids [15], biphasic system containing dendrimer-bound (achiral version) [16] or fluorous (achiral version) [17] osmium catalyst.…”
Section: Introductionmentioning
confidence: 99%